EFUSI PLEURA MALIGNA: DIAGNOSIS DAN PENATALAKSANAAN TERKINI - Ngurah Rai, I B (journal of internal medicine, 2009)
Malignant pleural effusions (MPE) are an important complication for patients with intra and extrathoracic malignancies.MPE are also a complication of far advanced malignancies or as the initial manifestations of an underlying malignancy, withmore than 150.000 cases/year in America. Median survival after diagnosis of an MPE is about 4 months. Although almost everytumor can cause it, more than 75% of MPE caused by malignancies at lung, breast, ovaries, mesotheliomas and lymphomas. Thestandard management approach begins with a diagnostic and or therapeutic thoracentesis. New imaging modalities help us todiagnose MPE, however positive cytologic conÞ rmation is necessary to establish a diagnosis. But, there are difÞ culties to Þ nd theetiology and deal with rapid recurrences of MPE. It is where several biomarkers took place in diagnosing MPE. Managementsof an MPE remain palliative. Several options include thoracenteses, pleurodesis, continuous outpatient drainage with indwellingcatheter, and pleuroperitoneal shunting. Recent studies focused on molecular marker and inß ammatory cytokine as a diagnostictool and target therapy for MPE. Many studies look for the role of EGFR (Epidermal Growth Factor Receptor), MCP-1 (monocytechemoattractant protein-1), VEGF (vascular endothelial growth factor), and TNF-  in diagnosing and possibly treat MPE.